Better-off women boosting groundnut business in Ghana - Akpo, E.; Ojiewo, Christopher Ochieng; Omoigui, L.O.; Rubyogo, Jean-Claude; Varshney, Rajeev K. (Springer, 2020)
Groundnut was one of the biggest breeding programs in Ghana in the mid-nineties, but the production declined because of many factors including the rosette disease and the fact that there was no dedicated breeder of groundnut for over 10 years. According to Dr. Roger Kanton, Deputy Director of CSIR-SARI (Council for Scientific and Industrial Research - Savanna Agricultural Research Institute), it was then, in 2015, with the support of the Tropical Legumes Projects that the groundnut breeding program was reinitiated. “Only a few local germplasms were available,” adds Dr. Richard Oteng-Frimpong, a young groundnut breeder, who came along with the support of the Tropical Legumes projects to start again the breeding program in 2015.